Working with Generative AI: We need more African Voices, Real African Voices - Abdulhamid, Najeeb G.; Nyairo, Stephanie; O'Neill, Jacki (2024)
Generative AI has taken the world by storm, appearing to be more usable than previous generations of AI. We describe the findings of a qualitative study of Small and Medium Businesses in Kenya and Nigeria who were using generative AI tools in their everyday work. We found that AI tools were used to support both mundane and creative work and provided both organisational and individual benefits. Participants adopted a number of methods to navigate the strengths and weaknesses of different tools and comparing the output of multiple tools was common. Additionally, our findings suggest that whilst to some extent rhetorics around the democratisation of AI might hold true, these tools did not well support or represent African languages, identities or locales and were understood by participants to embody Western biases. We propose that regional bias should be explicitly called out to encourage researchers to focus on these concerns.